Desain of Multilevel Wall Trap For Selectivity of the Capture Spiny Lobster - Abdullah, Agung Sobri; Suharyanto, Suharyanto; Soeboer, Deni Achmad (Newinera Publisher, 2025)
The challenge faced by fishermen involved in lobster fishing is the decline in population due to overfishing and unsustainable practices. Intensive lobster fishing can disrupt the balance of the ecosystem, especially if the fishing gear used is not environmentally friendly. Lost fishing gear can continue to catch lobsters and other species unintentionally, a phenomenon known as ghost fishing. The methods applied in this research include literature review and experimental design. The literature review was conducted by examining data and the development of lobster traps from research publications and various books related to fishing. The analysis of the development of existing trap designs before the modification process is a key factor in selecting the standard trap design. This aims to develop lobster traps that are selective for legal sizes. The tiered wall trap has two entrances, one at the top in the shape of a cylinder with a width of 15 cm and a length of 20 cm, cylindrical in shape and without any hole patterns. It is expected that the trapped lobsters will not be able to escape because the length of the entrance itself is longer than the leg size of the catchable lobsters, where lobsters with a carapace length of 8.3 cm have a front leg length of 8 cm, making it impossible for the caught lobsters to climb out. The design of the tiered wall trap with a perforated pattern on the base of the trap at 8 cm is expected to allow catchable lobsters to climb into the trap's mouth. The tiered walls help lobsters to easily climb up to the mouth, thereby increasing the effectiveness and selectivity of the trap for catchable-sized lobsters. However, this design still needs to be tested in lobster catching areas or in laboratory scale.